The Effect of Using a Neck Roll Pillow with a Sniffing Position on Oxygen Saturation in Post Operative Patients under General Anesthesia - Salma Nur Padilah; Marta Tania Gabriel Ching Cing; Budi Joko Santoso; Wahyu Riyaningrum (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2026)
Postoperative patients undergoing general anesthesia are at risk of decreased oxygen saturation during the early recovery phase due to reduced consciousness, muscle relaxation, and upper airway obstruction. This condition requires appropriate airway management to maintain airway patency. One non-pharmacological intervention that can be applied is patient positioning in the sniffing position with the assistance of a neck roll pillow to support proper head and nack aligment. This study aimed to analyze the effect of using a neck roll pillow in the sniffing position on oxygen saturation postoperative patients under general anesthesia. This research employed a quantitative method with a pre-experimental one-group pretest-posttest design. A total of 36 respondents were selected using purposive sampling in the recovery room of RSU PKU Muhammadiyah Aghisna Kroya. Oxygen saturation (SpO2) was measured before and after the intervention using a pulse oximeter. Data were analyzed using the Wilcoxon test due to non-normal data distribution. The results showed an increase in the mean oxygen saturation from 94.75% before the intervention to 99.22% after the intervention, with a p-value of 0.000 (p < 0.05). These findings indicate that the use of a neck roll pillow in the sniffing position has a significant effect on improving oxygen saturation in postoperative patients under general anesthesia. These findings are expected to be a simple, safe, and effective airway management intervention in the post-anesthesia recovery phase.